PENERAPAN MINIMUM SPANNING TREE DALAM PENGOPTIMALAN JARINGAN LISTRIK DI PERUMAHAN GRAND CILEGON RESIDENCE, JL. BOUGENVILLE - Aulia, Nindy Nur; Mustri, Pingki Avrillia Wandani; Wirabuana, Setyo Fiddin; Ramadhania, Sherin; Budiharjo, Budiharjo (LPPM Universitas Bina Bangsa, 2024)
Electrical networks are very useful in everyday life. The electricity network is one of the main resources, namely as a resource for all household and company electronic equipment and of course every house or company must have an electricity network. But how can all these points have an electricity network and that the network is neatly arranged and efficient? So researchers are conducting research which will discuss and analyze the optimization of the electricity network at Grand Cilegon Residence, Jl. Bougainvillea. The problem that we want to overcome is minimizing the path or length of the electricity network in the Grand Cilegon Residence Housing Complex, Jl. Bougainvillea. This research aims to be used as a consideration in installing electrical cables in the Grand Cilegon Residence housing complex and also as a comparison of the distance to the electricity network by obtaining the minimum distance to the electricity network so that the electricity network in the area can be installed neatly and efficiently. The research method used by researchers in network problems is the Minimum Spanning Tree (MST) model. Based on the analysis and calculations that have been carried out, the results obtained from this research are that the Grand Cilegon Residence housing only requires electrical cables with an optimal distance of 85 km. These results show that the use of the Minimum Spanning Tree (MST) model has a great influence on optimizing the distance connecting points. houses and other points by saving more on the use of electrical cables can be said to be effective and efficient